Factors Affecting Ultrasonographic Fetal Weight Estimation Accuracy in Low Birth Weight Newborns - Nevin Tuten; Onur Guralp; Koray Gok; Abdullah Tuten; Altay Gezer (Gynecology Obstetrics & Reproductive Medicine)
Objective: To investigate the accuracy of fetal weight estimation made by the last prenatal ultrasound measurement in low birth weight newborns (<2500 g).